Strange Quark Stars: The Role of Excluded Volume Effects - Lugones, G. (2024)
We study cold strange quark stars employing an enhanced version of the quark-massdensity-dependent model, which incorporates excluded volume effects to address non-perturbativeQCD repulsive interactions. We provide a comparative analysis of our mass formula parametrizationwith previous models from the literature. We identify the regions within the parameter spacewhere three-flavor quark matter is more stable than the most tightly bound atomic nucleus (stabilitywindow). Specifically, we show that excluded volume effects do not change the Gibbs freeenergy per baryon at zero pressure, rendering the stability window unaffected. The curves of pressureversus energy density exhibit various shapes—convex upward, concave downward, or nearlylinear—depending on the mass parametrization. This behavior results in different patterns of increase,decrease, or constancy in the speed of sound as a function of baryon number density. Weanalyze the mass–radius relationship of strange quark stars, revealing a significant increase in maximumgravitational mass and a shift in the curves toward larger radii as the excluded volume effectintensifies. Excluded volume effects render our models compatible with all modern astrophysicalconstraints, including the properties of the recently observed low-mass compact object HESSJ1731.